The predictive diagnostic value of serial daily bedside ultrasonography for severe dengue in Indonesian adults. - Meta Michels; Uun Sumardi; Quirijn de Mast; Hadi Jusuf; Mita Puspita; Intan Mauli Warma Dewi; Sylvia Sinarta; Bachti Alisjahbana; André J A M van der Ven (Public Library of Science (PLoS), 2013)
BACKGROUND: Identification of dengue patients at risk for progressing to severe disease is difficult. Significant plasma leakage is a hallmark of severe dengue infection which can suddenly lead to hypovolemic shock around the time of defervescence. We hypothesized that the detection of subclinical plasma leakage may identify those at risk for severe dengue. The aim of the study was to determine the predictive diagnostic value of serial ultrasonography for severe dengue. METHODOLOGY/PRINCIPAL FINDINGS: Daily bedside ultrasounds were performed with a handheld ultrasound device in a prospective cohort of adult Indonesians with dengue. Timing, localization and relation to dengue severity of the ultrasonography findings were determined, as well as the relation with serial hematocrit and albumin values. The severity of dengue was retrospectively determined by WHO 2009 criteria. A total of 66 patients with proven dengue infection were included in the study of whom 11 developed severe dengue. Presence of subclinical plasma leakage at enrollment had a positive predictive value of 35% and a negative predictive value of 90% for severe dengue. At enrollment, 55% of severe dengue cases already had subclinical plasma leakage, which increased to 91% during the subsequent days. Gallbladder wall edema was more pronounced in severe than in non-severe dengue patients and often preceded ascites/pleural effusion. Serial hematocrit and albumin measurements failed to identify plasma leakage and patients at risk for severe dengue. CONCLUSIONS/SIGNIFICANCE: Serial ultrasonography, in contrast to existing markers such as hematocrit, may better identify patients at risk for development of severe dengue. Patients with evidence of subclinical plasma leakage and/or an edematous gallbladder wall by ultrasonography merit intensive monitoring for development of complications.